Impact of straight to test pathways on time to diagnosis in oesophageal and gastric cancer. Issue 3 (21st July 2018) - Jones, James Andrew; Catton, James; Howard, Glen; Leeder, Paul; Brewer, Lesley; Hatton, James; Shaw, Dominick E
Abstract : Background: Cancer survival in the UK has doubled in the last 40 years; however, 1-year and 5-year survival rates are still lower than other countries. One cause may be a delay between referral into secondary care and subsequent investigation. We set out to evaluate the impact of a straight to test pathway (STTP) on time to diagnosis for upper gastrointestinal (UGI) cancer. Methods: Six hospital Trusts across the East Midlands Clinical Network introduced a STTP enabling general practitioners to refer patients with suspected UGI cancer (oesophageal/gastric) for immediate investigation, without the need to see a hospital specialist first. Data were collected for all patients referred between 2013 and 2015 with suspected UGI cancer and stratified by STTP or traditional referral pathway. Overall time from referral to diagnosis was compared. Data from two Trusts who did not implement STTP acted as control. Results: 340 patients followed the STTP pathway and 495 followed the traditional route. STTP saved a mean of 7 days from referral to treatment (with a 95% CI of 3 to 11 days, p<0.008) and a mean of 16 days from referral to diagnosis, when compared with a traditional referral pathway. The number of diagnostic tests performed using STTP or traditional referral pathways were similar. Conclusion: A STTP is associated with an overall reduction of 1 week from referral to treatment for UGI cancer. The approach is feasible and did not require more resource. Larger studies are required to assess whether this time saving translates into improved cancer outcomes.